From the Editor-in-Chief - John E. Paul (World Health & Population, 2013)
This issue of World Health & Population presents three original research papers that should be of great interest to our readers, in addition to a high-quality paper reprinted from the International Journal of Environmental Research and Public Health (IJERPH). The original papers have all been published online by WHP during the last quarter and are selected here as representative of recent outstanding contributions to the journal.